Effects of various alkali metal cations on the synthesis, crystallization and catalytic properties of NKX-2 aluminophosphites - Abdullahi, Haruna; Wong, Ka-Lun; Lim, Gin Keat; Awala, Hussein; Vicente, Aurélie; Ling, Tau Chuan; Mintova, Svetlana; Ng, Eng Poh (Elsevier, 2019)
Alkali metal-containing NKX-2 (M-NKX-2) aluminophosphite crystals were hydrothermally synthesized in the Al2O3–P2O5–M2O–H2O system for the first time using various alkali metal hydroxides (MOH: M = Li, Na, K, Cs). The results showed that NKX-2 crystalline phase could be obtained within several hours without using harmful organic amine structure-directing agent. In addition, the alkali metal hydroxides played an important role in controlling the crystallization rate and the morphology of M-NKX-2 particles in aqueous medium. The resulting M-NKX-2 solids possessed basicity which was catalytically active in base-catalyzed cyanoethylation reaction of methanol.